384 A Phase 1 study to evaluate the safety, PK, and antitumor activity of AK117, an anti-CD47 monoclonal antibody, in subjects with relapsed/refractory advanced or metastatic solid tumors or lymphomas. (9th November 2020) - Prawira, Amy; Coward, Jermaine; Mislang, Anna; Nagrial, Adnan; Gan, Hui; Jin, Xiaoping; Li, Baiyong; Wang, Zhongmin Maxwell; Kwek, Kon Yew; Xia, Dennis; Xia, Yu
Abstract : Background: AK117 is a novel humanized IgG4 monoclonal antibody (mAb) targeting CD47, a macrophage immune checkpoint and 'don't eat me' signal that allows tumor cells to evade immune destruction by phagocytic cells. Most human cancers express CD47 to varying degrees, making CD47 a universal target. The efficacy of anti-CD47 therapy has been studied, as monotherapy and in combination with other antineoplastic agents, in various malignancies, including acute myeloid leukemia, diffuse large B-cell lymphoma, multiple myeloma, colorectal cancer, hepatocellular carcinoma and breast cancer. Anemia is common with anti-CD47 therapy because CD47 is ubiquitously expressed on senescent red blood cells (RBCs). However, in comparison to other anti-CD7 mAbs, AK117 exhibits significantly weaker binding to human RBCs than tumor cells. In both in vitro and in vivo nonclinical studies, AK117 demonstrated robust anti-tumor activity without causing significant agglutination of human RBCs in vitro or anemia in monkeys. Methods: This is a first-in-human, Phase 1, multicenter, open label, single arm, dose escalation and dose expansion study of AK117 administered intravenously to adult subjects with relapsed/refractory advanced or metastatic solid tumors or lymphomas. The primary objective is to assess the safety and tolerability of AK117 monotherapy; and determine the maximum tolerated dose (MTD). Antitumor activity, PK, pharmacodynamic profile and immunogenicity of AK117 will be studied as secondary objectives.The dose escalation parts of the study uses a 3+3+3 design to determine the Recommended Phase 2 Dose (RP2D) dose between 0.3 mg/kg to 45 mg/kg QW. Dose escalation is performed exclusively in solid tumors; and any dose escalation cohort not exceeding the MTD may be expanded up to a maximum of approximately 18 subjects, with a minimum of 6 subjects with lymphomas, to provide additional clinical data to inform the optimal dose level and treatment schedule for tumor type-specific dose expansion and subsequent clinical studies. In the dose expansion phase, AK117 will be studied in cohorts of 30 subjects each with selected solid tumors and selected lymphomas.Subjects with active or prior autoimmune disease that may relapse, history of hemolytic anemia of any cause within 3 months of first dose, hemophagocytic lymphohistiocytosis, defects in RBC production; or defects in hemoglobin production or metabolism will not be eligible for this study. Results: N/A Conclusions: N/A Trial Registration: NCT04349969 Ethics Approval: The study was approved by Bellberry Human Research Ethics Committee (Application No. 2020-02-016).